Efektivitas Pasal 21 Ayat (2) Huruf E Undang-Undang Nomor 5 Tahun 1990 Tentang Konservasi Sumber Daya Alam Hayati dan Ekosistemnya dalam Perlindungan Penyu: Studi di Pantai Sungai Belacan Desa Sebubus Kecamatan Paloh - Putri, Dinda; Hasiah, Hasiah; Azmi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The turtle egg trade threatens the existence and population of turtles themselves. Until now, the trade in turtle eggs is still found in Sebubus Village. Turtle protection has been regulated in Law Number 5 of 1990 concerning Conservation of Biological Natural Resources and Their Ecosystems. There are two focus problems in this research, namely how to implement turtle conservation on the Belacan River Beach; and what is the effectiveness of article 21 paragraph (2) letter e of Law Number 5 of 1990 concerning Conservation of Biological Natural Resources and Ecosystems for the protection of turtles on the Belacan River Beach in Sebubus Village, where to date the theft and trade in turtle eggs is still rampant in Sebubus Village. The type of research is qualitative, namely by collecting data from the field and direct interaction with informants. The approach used is an empirical approach, namely looking at the application of the law based on facts in the field. To obtain research data, researchers used observation and documentation interview techniques. Based on the research results, it was found that the implementation of turtle conservation at Sungai Belacan Beach carried out by the Wahana Bahari Paloh Community Group was very good in reducing the level of turtle egg theft. That the effectiveness of Article 21 Paragraph (2) Letter e of Law Number 5 of 1990 concerning Conservation of Biological Natural Resources and Ecosystems in protecting turtles on Belacan River Beach, Sebubus Village, Paloh District, is still not effective. Research shows that there are still many cases of theft of turtle eggs which cause huge losses to the turtle population. The stolen eggs are then traded illegally. This condition shows that although there are clear regulations prohibiting the collection and trade of turtle eggs, their implementation is less effective in preventing these illegal cases.